Realizing the SDGs Through the Development of Islamic Finance: Its Impact on Environmental Quality, Economic Growth, and Population in All Provinces of Indonesia - Ivanka, Meitia; Siregar, Suci Wulandari; Dharmawan, Annisa Zahrina (Jurnal Magister Ekonomi Syariah, 2025)
Indonesia faces significant challenges in achieving sustainable development, amidst increasing air pollution, social inequality, and the need to improve public welfare. In efforts to optimize Islamic Financial Development (IFD) as an instrument to support the Sustainable Development Goals (SDGs), this study aims to explore its impact on Environmental Quality (EQ), Economic Growth (GDP), and Population (POP) across all provinces in Indonesia. Using the Panel Vector Error Correction Model (PVECM), the study finds that IFD has a negative effect on air quality (EQ), although this impact is not significant in both the short and long term. On the other hand, economic growth (GDP) shows a significant negative impact on environmental quality, with an increase in GDP contributing to a reduction in air pollution. Meanwhile, population (POP) has a significant negative impact on environmental quality, meaning that although an increase in population may worsen air quality, proper environmental policies can mitigate its negative effects. The findings of this study suggest that the integration of the Islamic finance sector with effective environmental policies is crucial for accelerating the achievement of SDGs in Indonesia, with attention to the specific characteristics of different regions.